KUISIONER PELAYANAN DAN PERKULIAHAN PADA SEKOLAH TINGGI MANAJEMEN INFORMATIKA DAN KOMPUTER (STMIK) INDONESIA PADANG BERBASIS WEB - Rajab -; Amuharnis - (JURNAL AKADEMIKA)
This research aims to simplify the Quality Assurance Agency (BAPEM) Internal in analyzing questionnaire data services and lectures and also facilitate the students in filling out the questionnaire and lecture services . The research was conducted on STMIK Indonesia Padang because each semester of BAPEM STMIK Indonesia Padang evaluate the faculty performance and service in the learning process. The process of filling the questionnaire is still done manually so that the officers visited every local to distribute the questionnaire. This study result the application of filling the questionnaire program and lecture services in STMIK Indonesia Padang and Web -based re-enroll students who will have to fill out the questionnaire first. If the questionnaire has been filled by the students through campus SISFO then autommatically the student could fill Study Plan Card ( KRS ). Nor vice versa, if the students did not fill out the questionnaire services and lectures, the students are not able to fill the KRS.